Between Informal Engagement and Classroom Passivity:: Understanding EFL Investment in Indonesian Islamic Boarding Schools - Destari, Herlin Putri Indah (Universitas Jambi, Magister Program of English Education Department, 2026)
This study explores the challenges influencing students’ investment in Indonesian Islamic boarding schools (pesantren), and how students negotiate these challenges. Drawing on Darvin and Norton’s (2015) model of investment, it examines qualitative data from focus group discussions with 29 students and semi-structured interviews with three English teachers from three pesantren schools in West Java. The findings reveal a discrepancy between learners’ high informal engagement with English and their limited classroom participation, which cannot be explained simply by low motivation or limited proficiency. In this context, learners’ investment is influenced by institutional regulations, pedagogical constraints, examination priorities, and moral discourses that frame English as both opportunity and ethical risk. Some cases show how learners may remain highly invested in English while strategically limiting their classroom participation when existing forms of engagement did not align with their aspirations or values. These cases suggest that classroom passivity may reflect a calculated negotiation rather than a lack of interest in the language. Theoretically, the findings add depth to existing investment theory by demonstrating how both teachers and learners in religious educational settings negotiate the perceived benefits of English against moral legitimacy. Pedagogically, the findings call for more dialogic approaches that recognise learners’ informal English experiences while remaining respectful to the moral boundaries. While serving as pedagogical filters to ensure the propriety of learning content, EFL teachers can design low-stakes communicative activities that encourage active communication and reflection for critical language awareness.